2013
DOI: 10.1016/j.rboe.2012.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary assessment of trauma patients in a hospital in the city of São Paulo: a question of necessity

Abstract: Objective To minimize the occurrence of missed injuries, the tertiary evaluation was introduced consisting of reassessment of the patient, 24 hours after admission, with: complete history, physical examination, review of exams and diagnostic testing if necessary. Methods Observational study evaluating trauma patients admitted to a teaching hospital in São Paulo, according to a protocol for tertiary evaluation. Results Between February and May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Studies have shown that head injuries (4, 6, 13, 14), mechanical ventilation (5, 8), low scores on the Glasgow Coma Scale (GCS) (2, 4, 7, 15), and high Injury Severity Scores (ISS) (2, 4, 7, 15, 16) can lead to delayed diagnosis. Inadequate clinical examinations (9, 11), departures from clinical routines (11), and misinterpreted or inadequate radiographs (2, 4, 5, 8, 11, 17) also contribute to delayed diagnoses. In addition, patients from road traffic accidents are more likely to have missed injuries (4, 8, 11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that head injuries (4, 6, 13, 14), mechanical ventilation (5, 8), low scores on the Glasgow Coma Scale (GCS) (2, 4, 7, 15), and high Injury Severity Scores (ISS) (2, 4, 7, 15, 16) can lead to delayed diagnosis. Inadequate clinical examinations (9, 11), departures from clinical routines (11), and misinterpreted or inadequate radiographs (2, 4, 5, 8, 11, 17) also contribute to delayed diagnoses. In addition, patients from road traffic accidents are more likely to have missed injuries (4, 8, 11).…”
Section: Introductionmentioning
confidence: 99%
“…According to the current literature, the incidence of missed injuries in trauma patients varies across different studies from 0.6% to 39% (116, 18, 19). These differences in the results may stem from differences between the study populations and methods, and especially from differences in the criteria which determine whether an injury has been missed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches to reduce the incidence rate of missed injuries and to identify the risk factors of missed injuries in initial survey have been performed actively. [ 6 , 7 , 8 , 11 ] Risk factors associated with undetected injuries include young age, high Injury Severity Score, polytrauma, absence of soft tissue injuries, and presence of chest or pelvic injuries. [ 12 ] Interestingly, young age was one of the significant risk factors of undetected injuries in emergency department in a retrospective cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] Some studies demonstrate that this protocol is beneficial for the detection of missed injuries. [ 7 , 11 ] One observational study reported that neglected lesions were observed in 11.5% patients in the protocol, [ 11 ] and another literature review study reported missed injury detection rates in several studies to be better in the tertiary survey group, compared to primary and secondary survey groups, showing detection rates of missed injuries varying from 2.6% to 30.96%. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%